Antioxidant Properties of Honey from Different Altitudes of Nepal Himalayas - Neupane Bishnu Prasad; Malla Komal Prasad; Kaundinnyayana Atis; Poudel Prakash; Thapa Rashmi; Shrestha Sabina (Polish Journal of Food and Nutrition Sciences, 2015)
Twenty two multifloral honey samples representing central western parts of Nepal were examined spectrophotometrically for their antioxidant properties and total phenol content. The modified Folin-Ciocalteu method was used to determine total phenol content and 2,2-diphenyl-1-picrylhydrazyl radicals (DPPH•) assay for antiradical activity. In all samples, physicochemical parameters like moisture, reducing sugar, sucrose, ash, free acidity and water insoluble matter were also measured according to harmonized methods of the International Honey Commission (IHC). The results of physicochemical analysis showed that all the values, except for moisture of a small number of high altitude honey samples, are in good agreement with the current Nepalese standard. The total phenolic contents of honey, collected from high and low altitude, ranged from 154.87 to 41.90 mg gallic acid equivalent (GAE/100 g) respectively, at corresponding antiradical activity using DPPH• expressed as percent inhibition of 76.66% and 25.69%. The IC50 values of selected high altitude honey samples ranged from 56 to 72 mg/mL. The total antioxidant properties were correlated (P<0.01) between total phenol content and antiradical activity (r=0.992). The obtained results demonstrate that the Nepalese honey collected from high altitude region contained more antioxidants than honey of low altitude region.